La inclusión escolar de alumnos(as) con necesidades educativas especiales y su incidencia en la interacción social con sus pares de cinco a seis años de edad, en las escuelas María Montessori y Manuel José Rodríguez, de la parroquia de Malacatos, Loja-Ecuador, durante el año lectivo 2011-2012. Lineamientos alternativos - Valarezo Alcivar, Carmen Belén (2014)
The central objective of this research is to analyze the school inclusion of students with special educational needs,end how is thesocial interaction with their parents, all those children are among five to six years, They are students from María Montessori and Manuel José Rodríguezschools, in this way to contribute to strengthening, firstly, determining, the strategies used by the teachers from both schools to realize the inclusion of students with Special Educational Need, on the other hand, establishing if the inclusion of students with SEN and students without special educational needs are affecting their social interactions that take place inside the classroom. The topic of Inclusive Education in the Context of Education for all, focuses on taking the problem from the diversity, unfortunately it is a systematic discrimination against people with special educational needs or people with and without disabilities, and all these problems are present in the education system.With the use of the methodology of scientific research with its different methods such as: induction, deduction and description as well as the application of different techniques investigated such as the survey, interview and the observation to the investigated population, alsoprincipals, teachers, parents, children five to six yearsfrom Maria Montessori and Manuel Jose Rodríguez schools were part of this investigation, taking in consideration that both schools carry on the school inclusion and its impact on children's social interaction, firstly,analyzingand then to present the needed conclusions and recommendations. On the other hand, based on the information obtainedit was determinedthat children of five tosix years belongs tothe investigated schools, the inclusive educationshould be partof a general strategy, so that the main goal be toachievea quality educationfor all, besides, the mentioned schools must engage withthe learning ofstudents withspecial educationalneeds, which representsa great challenge forhole school community, andalso a great opportunityfor teachersto growas professionalsandstrongeras a team. For students that present specialeducational needs, means learning fromandwith others,tohave the same opportunitiesto participatein the national curriculumwiththe rest of theirpartners inschool and social context they correspond. KEYWORDS: School Inclusion, Social Interaction, Special Educational Needs.